SIMULASI PEMBANGKITAN SINYAL 8–PHASE SHIFT KEYING BERBASIS MATLAB - Indah Susilawati (Universitas Ahmad Dahlan, 2009)
Phase Shift Keying (PSK) is simply the allocation of one fixed phase for every code in the bit streams. In BPSK modulation, it’s needed to allocate two distinct phases for “1” and “0”. In QPSK modulation, it’s needed to allocate four distinct phases, each for “01”, “01”, “10”, and “11”. While in 8 – PSK, it’s needed to allocate eight distinct phases, each for “000”, “001”, “010”, “011”, “100”, “101”, “110”, and “111”. Bandwidth efficiency in BPSK is 1 b/s/Hz and 2 b/s/Hz in QPSK. While in 8 – PSK, bandwidth efficiency achieved is 3 b/s/Hz. Higher efficiency bandwidth means narrower bandwidth needed for data transmission. This simulation is used to generate 8 - PSK signals using Matlab software tools. The results show that the simulation is able to generate BPSK and QPSK signals perfectly.